2018
DOI: 10.1186/s12886-018-0826-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of inverted internal limiting membrane (ILM) flap and ILM peeling technique in large macular holes: a randomized-control trial

Abstract: BackgroundThe anatomical success rate of macular hole surgery ranges around 93–98%. However, the prognosis of large macular holes is generally poor. The study was conducted to compare the anatomical and visual outcomes of Internal Limiting Membrane (ILM) peeling vis-a-vis inverted ILM flap for the treatment of idiopathic large Full-Thickness Macular Holes (FTMH).MethodsThis was a prospective randomized control trial. The study included patients with idiopathic FTMH, with a minimum diameter ranging from 600 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(80 citation statements)
references
References 37 publications
2
75
0
3
Order By: Relevance
“…In histopathologic findings, when the margins of the ILM were left attached to the edges of the hole, it served as a gap-free natural scaffold for gliosis, and provided a basement membrane for proliferateglial glial cells to maintain anatomic structure of the foveola [9,10]. Shiode et al showed that the neurotrophic factors and basic fibroblast growth factors (bFGF) on the surface of the ILM flap promoted the proliferation and migration of the Müller cells, contributing to fill the MH and enhance closure [11]. Activated Müller cells also produced neurotrophic factors and growth factors that may promote the survival of retinal neurons [18].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In histopathologic findings, when the margins of the ILM were left attached to the edges of the hole, it served as a gap-free natural scaffold for gliosis, and provided a basement membrane for proliferateglial glial cells to maintain anatomic structure of the foveola [9,10]. Shiode et al showed that the neurotrophic factors and basic fibroblast growth factors (bFGF) on the surface of the ILM flap promoted the proliferation and migration of the Müller cells, contributing to fill the MH and enhance closure [11]. Activated Müller cells also produced neurotrophic factors and growth factors that may promote the survival of retinal neurons [18].…”
Section: Discussionmentioning
confidence: 99%
“…The titles and abstracts reviewed, and the remaining 16 studies were retrieved for the next review. Finally, after reading carefully of full-texts, We included a total of 8 studies [4,[9][10][11][12][13][14][15], 4 RCTs [4, [9][10][11] and 4 case series [12][13][14][15]. Fig.…”
Section: Selection Of Studiesmentioning
confidence: 99%
See 3 more Smart Citations